การดูแลอาคารสำนักงานให้เช่าที่มีผู้เช่ารายเดียวกับผู้เช่าหลายราย โดยมีเจ้าของร่วมกัน : กรณีศึกษา อาคารกลาสเฮ้าส รัชดา และอาคารกลาสเฮ้าส สุขุมวิท - ศิริลักษณ์ ก่ำศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Leasing out office buildings is a business that requires a large investment to acquire buildings that are efficient and competitive in the market. Proper management of office buildings is also important and necessary. However, leasing patterns may affect the way the buildings are managed and may result in the use of different building management methods. This research study thus aims to compare the Glas Haus Building Ratchada, which has only one lessee and the Glas Haus Building Sukhumwit, which has several lessees. According to the research findings, the seven-storey GHBR has a total of 13,362.00 square meters in area. It is 21 years old and has a 29-person building management staff. The lessee is Thanachart Capital Public Company Limited. Meanwhile, the GHBS is 17-stories high, with a total of 26,651.50 square meters in area. While it is also 21 years old, the building management comprises 32 staff members and has 56 company lessees. The research results revealed that there were many differences in building management. The obvious difference that affected the workload and resulted in different work requirements was that with several lessees, greater effort was needed for finding people to rent. Other differences naturally resulted from the physical characteristics. The area around the GHBR features a parking lot and gardens while the parking space for the GHBS is in the building. As a result, the facilities management system and security are different. In addition, it was also found that the GHBR office space area is small and the proportioning of office space leased out is not clear cut. The space leased out thus included restroom areas and traffic areas. Both office buildings are owned by MBK Public Company Limited and both are managed by MBK Square Company Limited. While both buildings share the same administration, accounting, and finance, they have separate teams of building management and operations. As a result, it was found that the purchasing duties overlapped. It is thus recommended that the purchasing be consolidated and set up as a common work unit.